2017
DOI: 10.1002/lary.26669
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic plus electric speech processing: Long‐term results

Abstract: 2C. Laryngoscope, 128:473-481, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…More recent research has suggested that the use of acoustic information at and below 500 Hz is sufficient for providing the benefits of E+A stimulation described above. Table provides a summary of residual hearing using a three‐frequency LF PTA at 125 to 500 Hz, with the same 90 dB HL cutoff.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent research has suggested that the use of acoustic information at and below 500 Hz is sufficient for providing the benefits of E+A stimulation described above. Table provides a summary of residual hearing using a three‐frequency LF PTA at 125 to 500 Hz, with the same 90 dB HL cutoff.…”
Section: Resultsmentioning
confidence: 99%
“…Gantz et al recently reported that residual hearing could be preserved up to 15 years after Hybrid S8/S12 (Cochlear) device activation and up to 7 years in the case of Hybrid L24 (Cochlear). These authors examined results in subjects with the S8, S12, and L24 electrode arrays (S8 and S12 are 10‐mm electrode arrays, relative to the 16‐mm L24 array) and documented functional hearing in 83%, 92%, and 86% of subjects, respectively, at the most recent evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other manufacturers have also taken advantage of design features conducive to hearing preservation such as shorter, thinner and softer electrodes [18]. The MSE is somewhat shorter than its predecessor the 1j electrode (18.5 mm vs. 23 mm of intracochlear insertion length) [19], but due to its intended mid-scalar location the target insertion angle, according to the manufacturer’s claim, is comparable for both electrodes (420° for the MSE and 400° to 500° for the 1j) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of CI indications has resulted in an increasing number of patients with residual hearing receiving CIs . In this setting, preservation of residual hearing has become a clinical priority, and mechanisms by which this goal can be accomplished have become an area of intense focus.…”
Section: Discussionmentioning
confidence: 99%